Analysis of the impact of nuclear power plant on Malaysia's power systems: Costs, CO2 emission and system reliability - Dahlan, N. Y.; Ibrahim, A.; Rajemi, Mohamad Farizal; Mohd Nawi, Mohd Nasrun; Baharum, Faizal (2014)
Although Malaysia is blessed with plenty of fossil fuel and natural resources, but the amount of fossil fuels is now depleting.This has led Malaysia to find other alternative resources to generate electricity to meet the demand. Some possible options are: 1) Coal, however this leads to the dependency on imported coal and increases gas carbon emission, 2) Renewable energy (RE), however, the resources are interruptible and expensive, 3) Nuclear power plant, however the recent Fukushima incident and the public acceptance are the major consideration. Despite the nuclear safety that should not be compromised, nuclear power plant has many advantages over fossil fuel power plants.Nuclear power plant produces less CO2 emission, cheaper levelized cost than coal and gas power plants and can operate continuously for long hours. Ministry of Energy, Green Technology and Water Malaysia (KETTHA) targets the energy from nuclear in Malaysia will be 17.8% of total generation mix in 2030. This paper studies the impact of nuclear power plant on Malaysia's power system in 2030, in term of cost, CO2 emission and power system reliability. Two scenarios have been considered and compared; 1) Existing generation mix as in 2013, 2) Generation mix with nuclear as targeted by KETTHA in 2030. Results show that the generation mix with nuclear power plants has lower operation and investment cost, lower CO2 emission and higher system reliability.